Analisis Faktor –Faktor yang Mempengaruhi Turnover Intention Karyawan The Castle Garut - Indriyani, Anisa Putri; Widwi Handari Adji (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The purpose of this reaearch is find out what factors influence the castle shop turnover intention. There are several factors that cause the castle shop turnover intention. This study uses quantitative methond. SPSS V23 is used to analyze the data of 15 people who wrok in the castle shop as respondent in the study. According to the findings of this study,it has been determined that the castle shop for hiring new employees is affectd by all variables, including job satisfaction, salary, job stress, and organizational commitment. Together they have a good impact on turnover intention in research on salary, more attetion is paid to average employee compensatio, length of service and approriate needs for organizational commitmen, support and active role from the superiors of the castle shop are needed by building good relationships. Whith employees controlilng and evaluating employee job satisfaction so that they can alwyas improve company goals